The Influence of Implementing Canva-Based Learning Media on Students’ Learning Interest in Islamic Cultural History (SKI) Subject at Grade X MAPN 4 Medan - Sabila, Astri (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to investigate the influence of implementing Canva-based learning media on students’ learning interest in the Islamic Cultural History (SKI) subject at Grade X MAPN 4 Medan. The background of this research is the relatively low interest of students in SKI learning, which is often considered monotonous and conventional. This research employed a quantitative method with a quasi-experimental approach. The research instruments consisted of a student learning interest questionnaire and classroom observation sheets. Data were analyzed using a t-test to examine the difference in students’ learning interest before and after the implementation of Canva-based media. The findings reveal that the use of Canva learning media has a significant effect on increasing students’ learning interest. Therefore, Canva-based digital media can serve as an innovative alternative in SKI learning to create a more engaging, interactive, and digitally relevant classroom atmosphere.